The effect of interval training in children with exercise-induced asthma competing in soccer - Sidiropoulou, M. P.; Fotiadou, E. G.; Tsimaras, V. K.; Zakas, A. P.; Angelopoulou, N. A. (The Journal of Strength and Conditioning Research, 2007)
A lot of emphasis has been placed in screening individuals with exercise-induced bronchospasm in order to avoid persistence bronchial hyperactivity and consequent chronic silent inflammation of the respiratory tract. The purpose of this study was to evaluate the effect of interval training on the respiratory function and endurance in children with exercise-induced asthma (EIA) participating in the sport of soccer. Twenty-nine boys ages 10-14, who developed EIA after a 6-minute free running test (decline in forced expiratory volume in 1 second: FEV110%), participated in the study. They were divided into 2 groups (experimental: n = 18, and control: n = 11), fulfilling the same criteria (i.e., age, body height and weight, and severity of asthma). The experimental group exercised with the interval training method for a period of 8 weeks, (3 sessions per week), whereas the control group exercised with the usual football program. Measurements were made for FEV1 and endurance in both groups, before and after the application of training (8 weeks). Following the implementation of the training program, a significant improvement in FEV1 and endurance was documented in the experimental group, as well as significant differences between the 2 groups. In conclusion, duration and aerobic training via the interval method seems to be beneficial to soccer players with EIA.